Advanced Therapeutic Options for Treatment of Metastatic Castration Resistant Prostatic Adenocarcinoma - Naseer, Faiza; Ahmad, Tahir; Kousar, Kousain; Anjum, Sadia (Frontiers in Pharmacology, 2021)
The initial stage of prostatic adenocarcinoma (PaC) has been treated with surgery and radiation therapy, but the advanced stages need systemic novel treatment. Since 2010, several advanced therapeutic innovations have been introduced in various randomized clinical trials to improve survival and reduce morbidity and mortality. Several of these therapeutics have shown substantial survival assistance globally, even in the advanced stages of metastatic castration-resistant prostatic adenocarcinoma (mCRPC). This article describes advanced PaC therapy regimens including chemotherapeutic options, hormonal therapies (abiraterone, enzalutamide), immunotherapeutic agents, and bone-modifying agents. We discussed various pros and cons of gene therapy approaches including Crispr/Cas9 mediation, oncolytic viruses, suicidal genes, and micro-RNA based antitumor therapy. The mCRPC microenvironment is characterized by elevated prostate-specific antigen (PSA) levels, which ultimately trigger the androgen receptor (AR) and its dependent signaling pathways. The advanced therapeutics target these receptors and inhibit the steroidogenic enzymes that play an important role in increasing testosterone (T) and dihydrotestosterone (DHT) levels in the body. These advanced therapeutic novelties also target AR-independent oncogenic signaling pathways by focusing on DNA damage repair (DDR) pathways and their mechanisms. Some of these options appear to be very attractive strategies for acute and chronic stages of PaC and mCRPC treatment by overcoming the mechanisms of resistance.